2007
DOI: 10.4049/jimmunol.178.10.6073
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Role of B and T Lymphocyte Attenuator in Sustaining Cell Survival during Chronic Allostimulation

Abstract: B and T lymphocyte attenuator (BTLA; CD272) can deliver inhibitory signals to B and T cells upon binding its ligand herpesvirus entry mediator. Because CD28, CTLA-4, programmed death-1, and ICOS regulate the development of acute graft-vs-host disease (GVHD), we wished to assess if BTLA also played a role in this T cell-mediated response. In the nonirradiated parental-into-F1 model of acute GVHD, BTLA+/+ and BTLA−/− donor lymphocytes showed equivalent engraftment and expansion during the first week of the allor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 66 publications
8
88
1
Order By: Relevance
“…In agreement with the concept that BTLA functions as a prosurvival molecule for T cells is the fact that the engagement of BTLA on donor alloreactive T cells is required for their survival in a graft versus host disease murine model. 46,51 Thus, a single injection of an agonistic anti-BTLA antibody (clone 6A6) at the time of allogeneic bone marrow transplantation was sufficient to prevent GvHD through a mechanism that was mediated by donor Tregs. 51,52 The agonistic effect of the anti-BTLA antibody treatment and not the blockade of the interaction of HVEM/ BTLA on donor CD4 effector cells promoted a rapid contraction of the CD4 T-cell-mediated allogeneic immune response due to impaired survival of donor T cells expanding in response to lymphopenia in conditioned hosts and to an advantageous and competitive homeostatic expansion of Tregs that were responsible for prevention of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the concept that BTLA functions as a prosurvival molecule for T cells is the fact that the engagement of BTLA on donor alloreactive T cells is required for their survival in a graft versus host disease murine model. 46,51 Thus, a single injection of an agonistic anti-BTLA antibody (clone 6A6) at the time of allogeneic bone marrow transplantation was sufficient to prevent GvHD through a mechanism that was mediated by donor Tregs. 51,52 The agonistic effect of the anti-BTLA antibody treatment and not the blockade of the interaction of HVEM/ BTLA on donor CD4 effector cells promoted a rapid contraction of the CD4 T-cell-mediated allogeneic immune response due to impaired survival of donor T cells expanding in response to lymphopenia in conditioned hosts and to an advantageous and competitive homeostatic expansion of Tregs that were responsible for prevention of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This observation of impaired donor alloreactive BTLAdeficient T-cell survival during the course of Graft versus Host Disease (GvHD), which promotes the pathology resolution, indicates that BTLA may also play a role in alloreactive T-cell survival. 46 The BTLA/HVEM interaction is also essential for the homeostatic control of CD8a 2 dendritic cell numbers. Indeed, HVEM-and BTLA-deficient mice displayed an increased number of CD8a 2 dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…A prosurvival role of BTLA was initially observed in a chronic GvHD model in which adoptively transferred BTLA ¡/¡ splenocytes initially expanded in recipient mice but could not persist long term, suggesting that the memory T-cell function was compromised. 36 Recently, another study showed a prosurvival role of BTLA in vivo in a mouse model of vaccinia virus. 43 In this model, however, BTLA mediated survival and memory development through its expression on dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 In the platelet-derived growth factor (PDGF) receptor, this YXN motif has been found to bind to the signaling adaptor protein Grb-2 following phosphorylation of the tyrosine, leading to recruitment of phosphatidylinositol 3' kinase (PI-3K) and activation of Akt through serine phophorylation. 8,9,36 This suggests that HVEM-BTLA signaling could in fact have a prosurvival effect on TIL. To directly test whether BTLA ligation results in initiation of a prosurvival signal via phosphorylated Akt (pAkt), TIL were sorted into CD8 C BTLA C and CD8 C BTLA ¡ subsets and stimulated in vitro with HVEM-Fc fusion protein and anti-CD3 antibody.…”
Section: Btla Ligation Induces Pakt and Maintains Bad In A Phosphorylmentioning
confidence: 99%
“…For example, HVEM-BTLA pathway regulates acceptance of partially MHC-mismatched cardiac allograft [58]. BTLA expression was also found to be highly induced on anergic CD4+ T cells [59]. The treatment of mice infected with Plasmodium berghei ANKA with an agonist anti-BTLA mAb prevented the genesis of experimental cerebral malaria by restricting the number of T lymphocytes sequestered in the brain during infection [60].…”
Section: Functions In Host Defense Regulated By Tnfr Superfamilymentioning
confidence: 99%